Setting-aside cropland did not reduce greenhouse gas emissions from a drained peat soil in Sweden - Keck, Hannes; Meurer, Katharina H. E.; Jordan, Sabine; Kätterer, Thomas; Hadden, David; Grelle, Achim (Frontiers in Environmental Science, 2024)
In the process of their formation, northern peatlands were accumulating vast amounts of carbon (C). When drained for agricultural use, a large proportion of that C is oxidized and emitted as carbon dioxide (CO2), turning those peatlands to strong CO2 emitters. As a mitigation option, setting-aside farmland on drained peat is being incentivized by policies, but recent evidence casts doubt on these policies' efficiency for greenhouse gas (GHG) mitigation. To investigate the effects of setting-aside farmland on GHG fluxes from a Swedish peatland, we measured CO2, nitrous oxide (N2O), and methane (CH4) fluxes on two adjacent sites under contrasting management. The cultivated (CL) site was used for cereal production (wheat or barley) and the set-aside (SA) site was under permanent grassland. Carbon dioxide fluxes were measured from 2013 to 2019 using the eddy covariance (EC) method. Additionally, CO2, N2O, and CH4 fluxes were measured during the growing seasons of 2018 to 2020, using transparent and opaque chambers on vegetated plots and on bare peat. The cumulative CO2 fluxes measured by EC over the measurement period were 0.97 (±0.05) and 2.09 (±0.17) kg m -2 with annual average losses of 0.16 and 0.41 kg CO2 m -2 yr -1 for the CL and SA site, respectively. Thus, the SA site acted as a stronger CO2 source than the CL site. Both sites' contribution to global warming, calculated on basis of the chamber measurements, was dominated by CO2. The contribution of the SA site was higher than that of the CL site. Nitrous oxide emissions were low at both sites with higher emissions from the CL site for transparent measurements and measurements on bare peat. Whereas, CH4 uptake was highest on the SA grassland. Thus, on the basis of our study, we found no evidence that setting-aside farmland on shallow drained peat soils will reduce GHG emissions or even turn the peatland into a C sink.